(untitled) (Linguostylistic Studies, 2020)
The article highlights the peculiarities of the linguistic presentation of the hero’s inner state and considers it as one of the Lesia Ukrainka’s idiosyncrasy. On the material of the dramatic poem In the Field of Blood, the author traces the ways and means of linguistic disclosure of the Bible character Judas’ feelings and sufferings after the betrayal. The purpose of the research is to reveal the features of the linguistic objectification of the psychological state of the hero and the stylistic motivation of using them in the individual author’s style. It appears a marker of the poetess’s innovation in the context of the early twentieth century trends and inquiries. The method of associative-conceptual analysis was applied to measure the semantic capacity and stylistic loading of the fixed lexemes. The dynamics of the mental states are presented in the author’s comments and the main character’s speech. The means to convey feelings expression in the author’s directions/remarks include extralinguistic means (silence, pauses, laughter, a tempo of speech, voice and intonation), play on words, and description of the dynamic expressiveness. Verbal tools for expressing emotions are presented on lexical, grammatical, and stylistic levels. In Judas’ speech, emotionality is conveyed by colloquial words, phraseologisms with negative markers, the size and structure of remarks/replicas, exclamatory statements, objections, and rhetorical figures. Emotional comparisons, colorful and vivid epithets in characterization, much attention to the semantics of lexemes, and their author’s connotation testify to the mastery of Lesya Ukrainka in the linguistic development of the psycho-emotional state of the hero. The state of depression, exaltation, affect at the syntactic level is reproduced by remarks, different in size, structure, and complexity, in the form of exclamations, statements, objections, and rhetorical questions.